Damien - Frank, Jacquelyn (Frank, Jacquelyn. Nightwalkers., 2008)
In this third Nightwalkers installment, the Vampire Prince encounters a woman who tempts him with a desire unlike anything he has known. Together, they face a terrifying and relentless foe.